HUBUNGAN MOTIVASI DAN DUKUNGAN KELUARGA DALAM MELAKSANAKAN KELAS IBU HAMIL DI PUSKESMAS TALANG BANJAR KOTA JAMBI TAHUN 2017 - Dewi Riastawaty (Universitas Prima Indonesia, 2018)
Maternal Mortality Rate (MMR) in Indonesia from 1991 to 2007 was a very slow decline, from 2007-2012 an increase in MMR from 228 per 100.000 live births to 359 live births based on the latest Indonesian Demographic Health Survey (2012). The class of pregnant women is a means to leart together about health for pregnant women, in the from of face-to-face in groups and aimed to increase knowledge and skill of mothers on pregnancy, childbirth, postpartum care and newborn care, myths, infectious diseases and birth certificates. Based on the data of pregnant women at Puskesmas Talang Banjar in 2017, it is only 9 pregnant women who follow the class of pregnant women. This research applied a discriptive analytic approach in order to know the relationship of motivation and family support in the implementation of pregnant mothers class at Puskesmas Talang Banjar year 2017. The sampel in this study was taken in total sampling with 84 pregnant women. The data were collected by using questionaires and research data analyzed descriptively by using statistical of Chi-Square. The result of this research of 84 pregnant mothers found that 36 pregnant mother who follow the class is 41,7%, which did not follow as many as 49 that is 58,3% an in relation to poor family support in carrying class of pregnant mother that is 65,5% and with good support is 34,5%. The relationship of motivation with less good support in implementing pregnant mother class is 63,1% and good 36,9%. It is expected that paramedic and pregnant women should be able to improve the classroom of pregnant women’s class to improve the quality of public health.